Flexibility and changes in forms of workplace subjectivity: a case study of the South African automobile assembly industry - Barchiesi, Franco (My University, 2016)
This thesis is an investigation into worker responses to restructuring of work and production organisation in a South African automobile manufacturing company. The orgnnisation of work and production is analysed as part of managerial strategies aimed at promoting flexibility Worker responses will be conceptualized in a general model of worker subjectivity. Subjectivity here means the process through which workers make sense of changes in factory life according to regulative ideas and general moral and cultural constructions of the meanings of industrial work. I adopted a method based on observational research and semi-structured interviews with a group of workers, integrated by archival research and interviews with managers and union organisers, The results of my enquiry confirm hypotheses and theoretical frameworks critical towards the notion of flexibility as representing a clear divide with traditional "mass production" methods. In fact, managerial promotion of flexibility coexists here with relevant continuities in hierarchical and authoritarian structures, paternalism, lack of skills' recognition, use of technology as a mainly cost-cutting device, routinisation and lack of worker responsibility and independence. [Abbreviated Abstract. Open document to view full version]
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in fulfilment of requirements for the degree of Master of Arts in Sociology. Johannesburg, 1997.
Keywords: Automobile industry and trade -- South Africa.; Automobile industry workers -- Labor unions -- South Africa.